Excavations of the Twardowice Plateau (Silesian Upland) as refuges for xerothermic plant species - Babczyńska-Sendek, Beata; Błońska, Agnieszka; Kołtuniak, Anna (Biodiversity: Research and Conservation, 2013)
Paper concerns the flora of excavations from the area of the Twardowice Plateau, one of the regions of the Silesian Upland. These are rather shallow and small pits, which are remnants of exploitation of Triassic limestone and, rarely, iron ore. The studies showed that these excavations are the places where many species of vascular plants occurred. Xerothermic plants, which penetrated from adjacent grasslands, form the largest group (33%) among the 212 noted species. Some of them occurred much more frequently in the excavations than in the grasslands and some were found only in the excavations. It should be emphasized that 8 protected species were present in the investigated objects. Results from the Twardowice Plateau proved that many xerothermic plants could find suitable conditions for growth and survival in limestone excavations.